If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 34) = (7x + 10) Reorder the terms: (34 + 4x) = (7x + 10) Remove parenthesis around (34 + 4x) 34 + 4x = (7x + 10) Reorder the terms: 34 + 4x = (10 + 7x) Remove parenthesis around (10 + 7x) 34 + 4x = 10 + 7x Solving 34 + 4x = 10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 34 + 4x + -7x = 10 + 7x + -7x Combine like terms: 4x + -7x = -3x 34 + -3x = 10 + 7x + -7x Combine like terms: 7x + -7x = 0 34 + -3x = 10 + 0 34 + -3x = 10 Add '-34' to each side of the equation. 34 + -34 + -3x = 10 + -34 Combine like terms: 34 + -34 = 0 0 + -3x = 10 + -34 -3x = 10 + -34 Combine like terms: 10 + -34 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 9y+5y+20=62 | | 3x-10x+16=9-12x-28 | | 6(x-1)=3(x+1) | | 5xy(x+y)= | | (y-2)(y+4)=0 | | 6=2(7-c) | | y=16-6 | | 8-23x-14=9x-30x-6 | | 25-1.25x=16-.5x | | 15x-20=14x-21 | | 7+x(4)=16 | | -5n-8=16m | | 4x-5-6=12x-x-4-3x-7 | | 10n=9n+27 | | 24-8x=-2x+-10 | | x-(3x+7)=29 | | d-1=-9 | | 4x+(-4x)-2y+2y=-10+(-12) | | x+26-8x=8-4x | | 3x-6=60 | | q-e-(-2)=7-q | | 36=39 | | x^3-4x^2-11x+2=0 | | (2x+56)=(8x+8) | | 6x-18=30-2x | | w^2+6w+14=0 | | 2(x+8)=2x+16 | | 4.9x^2-93.3x-125=0 | | 4x^2-13x+12=-2x+12 | | -5-3p=-5(1-7p) | | 37-2x=7x+20 | | 5x+18=13x-82 |